Mathematical Aspects of Fluid Mechanics 2012
DOI: 10.1017/cbo9781139235792.010
|View full text |Cite
|
Sign up to set email alerts
|

Stretching and folding diagnostics in solutions three-dimensional Euler and Navier–Stokes equations

Abstract: Two possible diagnostics of stretching and folding (S&F) in fluid flows are discussed, based on the dynamics of the gradient of potential vorticity (q = ω · ∇θ) associated with solutions of the three-dimensional Euler and Navier-Stokes equations. The vector B = ∇q × ∇θ satisfies the same type of stretching and folding equation as that for the vorticity field ω in the incompressible Euler equations (Gibbon & Holm, 2010). The quantity θ may be chosen as the potential temperature for the stratified, rotating Eule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…The local conservation law form for the 'potential vorticity' is equivalent to the formula (3.9) derived using a direct method, with Θ ≡ F. The potential vorticity was used to study quasi-conservation laws for compressible Navier-Stokes equations in Gibbon & Holm (2012a), with the mass density ρ used in the place of the arbitrary function F. From the physical point of view, it is interesting to note that, in the latter paper, it was observed that, in the resulting conservation law, the pressure and other thermodynamic terms cancel completely, without any further simplification, such as the barotropic approximation. The dynamics of the gradient of the potential vorticity was considered in Gibbon & Holm (2010, 2012b; possible applications to atmospheric analysed data at the tropopause were discussed.…”
Section: Preliminary Discussionmentioning
confidence: 99%
“…The local conservation law form for the 'potential vorticity' is equivalent to the formula (3.9) derived using a direct method, with Θ ≡ F. The potential vorticity was used to study quasi-conservation laws for compressible Navier-Stokes equations in Gibbon & Holm (2012a), with the mass density ρ used in the place of the arbitrary function F. From the physical point of view, it is interesting to note that, in the latter paper, it was observed that, in the resulting conservation law, the pressure and other thermodynamic terms cancel completely, without any further simplification, such as the barotropic approximation. The dynamics of the gradient of the potential vorticity was considered in Gibbon & Holm (2010, 2012b; possible applications to atmospheric analysed data at the tropopause were discussed.…”
Section: Preliminary Discussionmentioning
confidence: 99%
“…Remark 2.13. A dual version of theorem 2.12, stating in our notation that the cross product between the gradients of two constants of motion must be a symmetry, has been applied to fluid models in [16][17][18][19]. Also, a result analogous to theorem 2.11, stating that the Lie derivative of a constant of motion along a symmetry is a constant of motion, is well known [6] and has been applied to fluid equations recently [20].…”
Section: Theorem 211 (Construction Of New Symmetries Starting From Kn...mentioning
confidence: 99%
“…Likewise in later sections we also discuss the compressible case in the same spirit. This paper aims to marry the ideas on stretching and folding processes in incompressible flows developed by the authors in [13,14] with their work on compressible flows [15]. Here, two forms of the projection of the vorticity ω onto the gradient of the mass density ρ(x, t) are discussed in §2.…”
Section: Stretching and Folding In The Incompressible 3d Euler Equationsmentioning
confidence: 99%
“…Namely, the projections within q = ω · ∇ρ and q = ω · ∇(ln ρ) cannot be transported 1 by the pseudo-velocity U q across level sets of the mass density, ρ. These equations may also be useful in the study of stretching and folding in compressible fluid flows, as investigated in the atmospheric context in [13,14].…”
Section: Physical Interpretation?mentioning
confidence: 99%